Occurrence of campylobacter and Salmonella Spp. in ostrich. - Yew, Ee Ling; Abdul Aziz, Saleha; Abu, Jalila (2011)
Campylobacter spp. and Salmonella spp. are important pathogens in veterinary medicine and public health. In Malaysia, there has been limited research done in ostriches due to the small-scale farming and small number of animals. Nevertheless, ostrich farming has a huge potential. Some of the disease agents affecting ostriches, such as Campylobacter spp. and Salmonella spp. can also cause disease in humans. As such, infected ostrich may serve as potential public health risk. Hence, this study was undertaken to determine the occurrence of Campylobacter spp. and Salmonella spp. in ostrich and this is the first report documenting the occurrence of these two bacteria in ostrich in Malaysia.Samples were collected from three ostrich show farms, with 8 ostriches from Farm A, 11 from Farm B and 12 from farm C. Samples from the cloaca and skin swabs were obtained from each of the ostrich and examined for Campylobacter spp. and Salmonella spp. All samples were cultured for Campylobacter spp. via direct plating on CCDA. One out of 62 samples (1.6%) was positive for Campylobacter spp. and it was isolated from the cloacal swab. Pre-enrichment, enrichment and direct plating on XLT4 and Salmonella Chromogenic agar were done for isolation of Salmonella spp. from the ostriches. Two samples, one from the skin swab and another one from the cloacal swab, from two different birds were positive for Salmonella spp. The study showed the occurrence of Campylobacter spp. and Salmonella spp. in ostriches. The ostrich is of public health significance as they are used in recreational activities and for human consumption.